The Influence of Brand Ambassado and Content Marketing on Interest in Halal Skincare Consumer Case Study of Scarlet Whitening Product - Windy Fatmawati (ASIAN PUBLISHER, 2023)
Scarlett Whitening is one of the well-known local skin care products. Which is successful and much in demand by the community. Scarlett Whitening has released many skincare products using the latest trending technologies. As with other skincare businesses, Scarlett Whitening wants its product sales to continue to increase. Scarlett Whitening tries to attract consumers through brand ambassadors and content marketing in this digital era. Therefore, this study aims to describe the influence of brand ambassadors and content marketing on the purchase intention of Scarlett Whitening. Researchers used descriptive quantitative methods. The population in this study is the younger generation. The sample used was 34 female students of UIN K.H. Abdurrahman Wahid Pekalongan. Researchers collect data sourced from primary and secondary data. Researchers obtained primary data from respondents' answers to the five Likert scale questionnaire. Meanwhile, secondary data comes from books, journals, and news portals that are relevant to this case. The analysis technique used in this study is multiple linear regression using SPSS software. The results of this study indicate that brand ambassadors have no significant effect on consumer interest in Scarlett Whitening. The popularity that has become the strength of brand ambassadors has not been able to influence consumer interest. Content marketing has a significant effect on consumer interest in Scarlett Whitening. Content marketing also shows a positive influence on consumer interest. Scarlett Whitening presents attractive marketing content according to consumer trends and needs. Thus, this affects consumer interest in making transactions for Scarlett Whitening products.